Two decades of change in cultural values and economic development in eight East Asian and Pacific Island nations - Allen, Michael W.; Ng, Sik Hung; Ikeda, Ken'Ichi; Jawan, Jayum; Sufi, Anwarul Hasan; Wilson, Marc S.; Yang, Kuo Shu (Sage Publications, 2007)
In a 1982 publication, Ng et al. surveyed the cultural values of select East Asian and Pacific Island nations. In 2002, this study repeated their work, using the same sampling frame, questionnaire, and collaborators, where possible. The authors also reclassified the 1982 and 2002 survey results using Schwartz's cultural-level value dimensions. Submission versus Dionysian values that differentiated the nations in 1982 continued to do so in 2002. Furthermore, nations that endorsed Mastery (and rejected Harmony) in 1982 experienced greater subsequent economic growth than did the other countries. Moreover, economic development in 1982 predicted ensuing changes in Submission versus Dionysian and Hierarchy versus Egalitarianism values. Richer nations tended to endorse Dionysian, Autonomy, and Egalitarianism, whereas poorer nations tended toward Submission, Embeddedness, and Hierarchy values. Overall, the results support both economic and cultural determinism and imply two opposing directions of cultural change.